Immunonutrition of Broilers Challenged with Eimeria spp. and Fed with Organic Acids as an Alternative to Chemotherapeutics - da Silva , Kelry Mayara; Araujo, Robert Guaracy Aparecido Cardoso; Oka, Claudia Harumi; Barbieri, Adriano; Barbosa, Bárbara Fernanda da Silva; de Lima, Gabrieli Andressa; Yamada, Paulo Henrique; Biller, Jaqueline Dalbello; Madeira, Alda Maria Back Noronha; Cruz-Polycarpo, Valquíria Cação (International Journal of Poultry Science, 2021)
Objective: This study was designed to evaluated the effect of organic acids as an alternative to chemotherapeutics in diets of broilers challenged with Eimeria spp. on their performance and immune system. Materials and Methods: A total of 840 male Cobb broiler chicks were utilized. The treatments were: basal diet, without additive (BD)-unchallenged birds; BD-challenged birds; BD+organic acids-challenged birds; BD+antibiotic and anticoccidial-challenged birds. The organic acids were a blend consisting of lactic acid (40%), propionic acid (5%) and butyric acid (1%). The birds were challenged by oral inoculation at the age of 11 days with E. acervulina, E. maxima and E. tenella. The performance was evaluated in the periods of 1-7, 1-14, 1-21 and 1-42 day. Blood from previously identified birds were collected on day zero, at three and at 10 days post-inoculation for immunological analyses. Results: The organic acids did not increase the performance of the challenged birds. They only showed a small improvement in the viability (VB), which provided an intermediate result between the control diet and the diet supplemented with the antibiotics. On day zero, it was observed from hemogram of the birds that the treatment had no effect on erythrocytes, hematocrit and hemoglobin. The microbiological challenge decreased the number of erythrocytes and the additives did not provide any improvement. These results evidenced an increase in the immune system response with the use of antibiotics, which fight against pathogenic microorganisms in the gastrointestinal tract (GIT). Although Eimeria challenge affects performance, even then, it was not possible to demonstrate a difference between the unchallenged and the challenged control in the immunological study. Conclusion: Diet supplemented with organic acids or antibiotics did not improve the broiler performance and few immunological changes were observed when inoculated with Eimerias.